Study on failure/fracture mechanisms of 3D printed objects by FDM with AE method (Evaluation by using Empirical Mode Decomposition and Chaos analysis) - TAKUMA, Masanori; TSUJII, Koki; SAITOH, Ken-ichi; TAKAHASHI, Yoshimasa; SATO, Tomohiro; NIKI, Yutaka (Kikai Gakkai ronbunshū = Transactions of the Japan Society of Mechanical Engineers, 2024)
The 3D printer using Fused Deposition Modeling (FDM) is attracting attention as a manufacturing technology that is able to reduce the production time and the manufacturing costs. However, the information on the mechanical properties and the process parameters that affect to the safety and the reliability of the shaped object is less than that for metallic materials. Therefore, it is desirable to detect and evaluate the phenomena such as “Craze occurrence/growth” and “In- or Inter-layer failure/fracture”. In this study, tensile tests were conducted to the two type specimens with different stacking directions. Then, it was attempted to extract the characteristics of those phenomena from the results of chaos analysis of AE signals detected during the test. The following findings were made clear. (1) The frequency ranges that characterize the respective phenomena were determined. (2) The chaos parameters of AE waveforms in which the signals were separated into the frequency range of each phenomenon using the Empirical Mode Decomposition (EMD), enabled the characteristics of that phenomenon. (3) Differences in stacking direction affect the chaotic characteristics of AE waveforms emitted by each phenomenon.